The Probability is not probabilism:: a dispute about the philosophical foundations of the Peruvian colonial economy (16th-17th centuries) and the modern economy of the 18th century - Martel Paredes, Victor Hugo (2023)
The distance that separates the traditions that give rise to the Peruvian economic system and the Great Britain economic system in the 18th century lies in the depths of modern mathematical reason and the inscrutable Peruvian colonial moral conscience. Nevertheless, there are theories that propose that the scholastic probabilism has been the source from which contemporary economic probability arose. The purpose of this article is to answer negatively to this hypothesis. This research is exploratory, but the analysis of the historical and economic texts will contribute to the confrontation of the hypothesis raised from philosophical theories that are formulated. Therefore, the method that has been used is demonstrative analytical. In sum up, the colonial economy cannot be thought mathematically, as in the case of probability, but rather in moral sense, which foundation was the probabilism that flourished in the newly discovered lands.